Testing Axioms of Revealed Preference in Stata - Marcos Demetry; Per Hjertstrand; Matthew Polisson (Research Institute of Industrial Economics (IFN), 2020)
This paper introduces the Stata commands checkax, aei, and powers as a bundle within the package rpaxioms. The first command allows the user to test whether consumer demand data satisfy a number of revealed preference axioms at a given efficiency level, the second command calculates measures of goodness-of-fit when the data violate these axioms, and the third command calculates power against uniformly random behavior as well as predictive success for each axiom at any given efficiency level. The commands are illustrated using experimental individual-level data and aggregated household-level consumption data.
Keywords: C87; D12; 330; Rpaxioms; Checkax; Aei; Powerps; Afriat effciency index; GARP; Revealed preference; Power; Predictive success